Introducing The Theory Of Inclusive Adaptation Cooperation To Inclusive Education And Its Skills - Masodiqova D. R. (Euro Asian Journal Publishing, 2024)
In this article, a new, modern and non-standard approach, i.e. "Inclusive Diffuse" scientific theory, the methodology, mechanism and possibility of its implementation, put forward by the author in the creation of a suitable process aimed at improving the quality and efficiency of inclusive education, stabilizing the socialization and integration of students with disabilities and perspectives are highlighted.
Keywords: Inclusive education; physical law; diffusion